REDUCING ROAD FREIGHT TRANSPORT CARBONISATION LEVEL AND PROBLEMS OF "GREEN FINANCING" BY COMMERCIAL BANKS IN LATVIA - Inna Stetsenko; Andrey Surmatch; Evelina Surmatch (Baltic Journal of Economic Studies, 2025)
In this article, the authors shall conduct a study of the impact of road freight transport on air pollution. The objective of the present study is twofold. Firstly, it seeks to reduce carbon emissions from road freight transport in Latvia. Secondly, it aims to encourage Latvian commercial banks to offer "green financing". In the course of the study, the following hypotheses were proposed by the authors: there is a correlation between the volume of investments in environmental protection and the EURIBOR interest rate; environmental pollution is dependent on the EURIBOR interest rate. The authors have demonstrated that 74% of the Latvian truck fleet has a high level of wear and tear, which shall lead to an increase in CO2 air pollution. This could be a potential avenue for the "green financing" facilitated by commercial banks. However, the commercial banks have declined to provide financing for "green projects" due to the perceived instability of the regulatory framework and the associated political risks. Consequently, "green financing" has been classified within the "high risk" category, which, in turn, necessitates the implementation of higher interest rates. In the context of the instability of business activity in the field of road freight transport, the risk of non-repayment of borrowed funds is increased. The following methodologies were employed in conducting the study: firstly, an empirical approach was adopted in the form of a modified group discussion, with the accompanying literature study constituting the initial phase of triangulation as a study strategy. This has enabled the formulation of hypotheses. In the subsequent phase of the triangulation process, a quantitative preliminary study of statistical indicators has been conducted. The indicators encompass the volume of road freight transport, air pollution, the service life of the truck fleet, the volume of environmental financing and the EURIBOR interest rate. The primary objective of the quantitative preliminary and main study has been the empirical collection of reproducible data. The present study employs a partial least squares structural equation modelling (PLS-SEM) approach for the purpose of testing the hypotheses that have been proposed. The objective of this procedure has been to investigate cause-and-effect relationships.